Regulatory efficacy of scopoletin, a biocoumarin on aortic oxido lipidemic stress through antioxidant potency as well as suppression of mRNA expression of inos gene in hypercholesterolemic rats - Nordin, Simbak; U.S. Mahadeva, Rao; C. Shanmuga, Sundaram (2015)
Preceding work in our laboratory has revealed that scopoletin, one of the main bioactive coumarin from fruits of Morinda citrifolia, exerts anti-diabetic activity in in vitro partly by averting α glucosidase and α amylase action. However, its aorto/vaso protective impact-based research is still incomprehensible. The present study looks into the regulatory efficacy of scopoletin on aortic lipid profile, radical scavenging status, endothelial factors and aortic morphology in dyslipidemic rats. Rats fed with normal diet serve as control [Group (G) 1], rats fed with cholesterolenriched diet (CED) (4 % cholesterol and 1 % cholic acid) for 45 days (G2), rats fed with CED for 45 days + scopoletin (10 mg/kg, body weight/day orally) for the last 30 days (G3) and scopoletin alone rats (G4). Blood and aortic tissue were taken immediately and used for various biochemical, histological and molecular analyses. A pronounced increase in the levels of aortic lipid profile, lipid peroxidation along with substantial suppression in the activities of aortic antioxidant and endothelial factor was observed in G2. The mRNA expression levels of iNOS gene were significantly up-regulated in aortic tissue of G2. On treatment with scopoletin, all the levels were reverted to near normalcy G3. Morphology of aorta in G2 indicated numerous foam cells with intimal changes, whereas the aorta of G3 exhibited fewer foam cells with normal intima. These results support that scopoletin expressively represses the aortic oxido-lipidemic stress and thereby upholding normal morphology of the aorta, and thus minimizing the peril of CVD.